Karakteristik Pengunjung di Ruang Publik Kota Mara - Hartina Alwi; Slamet Trisutomo; Mukti Ali (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2014)
This study determines the perceptions and preferences of visitors to the public space facilities in the Kota Mara. This research used qualititave and quantitative research. The numbers of samples of this research are 210. Samples selection used nonprobability purposive sampling technique by means of type purposive and accidental sampling. Data were collected by observation method and questionnaire with Likert Scale. Data analysis methods used was the frequency distribution analysis and multinomial regression analysis.This research aimed to khow how the characteristic of the visitors in Public Space of Kota Mara. The results of this study outlines that 1) Based on social characteristics of visitor Kota Mara is dominated by adult (17-25 years). The majority gender of visitor is male, background of educational is undergraduate student and the majority of background job is student. 2) Based on visiting characteristics of visitor Kota Mara are dominated by the visiting is not the first time, with the purpose of the visit to relax/hang out with friends or family, and the majority of the intensity of the visit is 2-7 times a week.